PELATIHAN PROGRAM EVIEWS UNTUK MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS WIRARAJA SEBAGAI SARANA UNTUK MENINGKATKAN KUALITAS PENELITIAN - Mohammad Rofik; Isyanto Isyanto (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2020)
Research is an obligation for every student who is at the peak of education, the peak is normally there in the fourth year since students take studying, so it becomes compulsory to write a research as a prerequisite to get a bachelor's degree. In writing a research course it will be faced with a method that will later be used in research. One such method is the quantitative method using Eviews 10 analysis tools. This tool can help students to process and analyze data quantitatively so that they will get quantitative conclusions as well, of course. This service is online method because it is related to an unfinished pandemic but that does not dampen students' intention to remain amnil part in learning. The obstacle faced in carrying out the service is that students only take the material but do not collect the assignments given.